ANALISIS PENGELASAN KOMBINASI GMAW DAN FCAW PADA BAJA ASTM A36 TERHADAP SIFAT MEKANI - Manta, Faisal; Wiguna, Ahmad Zulfikar Patria; Pratama, Kafinra; Haliq, Ridwan (ELEMEN : JURNAL TEKNIK MESIN, 2024)
A36 steel as raw material for heavy equipment attachments, such as blades and buckets. Gas Metal Arc Welding (GMAW) and Flux-Cored Arc Welding (FCAW) are used for the connection. High heat input and weld metal protection mechanisms are suitable for joining thick plates, however, in the field, malfunctions were found due to damage to the weld joint. To overcome this problem, research was carried out on two welding techniques to obtain optimal joint strength values. The research uses GMAW, FCAW and combination welding to join A36 steel with a V-beam angle of 60°. On the welding results, Magnetic Particle Inspection (MPI) and bending tests will be carried out. MPI testing states combination welding meets the requirements of the AWS1015 standard. The highest bending strength in FCAW welding was 160,419 MPa and the lowest in GMAW was 71,724 MPa, while combination welding was 113,312 MPa. The difference in value is influenced by the phases formed from each welding method visible in the microphotographs in the weld metal, HAZ and base metal areas.